Authority And Freedom. (December 2021) - Parsons, Michael
Authority and freedom are connected, and both have external and internal forms. External authority, political or institutional, can impinge on internal freedom in ways that matter to psychoanalysts. Internal freedom requires an internal authority that can be trusted. The superego is an external authority masquerading as an internal one. The ego, with its compliance toward the id, the superego, and external reality, operates like a false self in the psyche. In Lacanian terms, it is of necessity alienated from itself. By contrast, the true self as described by Winnicott, and the "subject" as theorized especially in French psychoanalysis, represent an authentic conscience that allows us to become the authors of our at one's authority. This implies two sorts of freedom: freedom from narcissistic self-investment, and the forward-looking freedom of psychic growth. The latter occurs only in a context of relatedness to others, and it entails caring for the interests of others—if necessary at one's own expense. This vision of human beings as having an innate impetus toward psychic growth makes psychoanalysis a fundamentally optimistic endeavor. Clinical and nonclinical examples show, however, that it demands a perpetual readiness to let go of apparent certainties.